THE INFLUENCE OF CURRENT RATIO AND RETURN ONASSETS TOWARDS THECAPITAL STRUCTURE (DEBT TOASEETS RATIO) ON THE COMPANY'SADVERTISING, MEDIAAND THE PRINTING OF REGISTERED IN THE INDONESIA STOCK EXCHANGE - Dody Firman (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Capital structure is a consideration between tang long term with its own capital which aims to maximise wealth for their owners. Where the capital structure is a complex financial decisions and understand its relationship with risk/return results, and value. The greater the debt to maendanai asset, then the greater the capital structure. Therefore a financial manager should pay attention to factors that affect and what impact good or bad for the company. The study aims to find out the influence of the Current Capital structure Ratio (DAR) and Return On Assets towards the capital structure (DAR) on the company's Advertising, Media and Printing are listed at the IDX. The approach used is the associative approach, with an urban sample and as many as 8 company Advertising, Media and Printing are listed in BEI 2011-2015 period. The sample used is purposive sampling. Technique of data analysis using the method of linear regression, the classical assumptions of multiple, test t (partial), the f-test (simultaneous) and the coefficient of determinsi with the help of the software SPSS version 16. The results showed that there was no influence parisal in Current Capital structure Ratio (DAR) and the value of sig 0.076, there is the influence of Return On Assets against the capital structure (DAR) and the value of sig 0.025. The results showed that there is a simultaneous influence of Current Ratio and Return On Assets towards the capital structure (DAR) and the value of sig 0.011. The magnitude of the coefficient of determination (R-Square) was amounting to 0.956. This shows that 95.6% of the dependent variable i.e. capital structure (DAR) can be explained by the independent variables namely Current Ratio and Return On Assets while the rest of 4.4% is affected by other variables that are not examined by this study.